Debt is Not Always Bad Even in Difficult Economic Conditions - Sandro Torang Hamonangan Sirait; Said Kelana Asnawi; Hendrian (Indonesian Journal of Business Analytics, 2024)
The problem faced by the company is the use of debt that is not according to plan. The purpose of this study is to determine whether debt policy affects company performance. This study was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange in 2018–2023 with a population of 296 companies, the sample used was 73 companies for six years. Thus, the number of samples used in this study was 438. The company performance variable is proxied by (ROE) while the independent variables in this study are debt policy proxied by (DER and DER*KE), investment decisions (KI), managerial ownership (MNJR), and economic conditions (KE). The data analysis method uses multiple linear regression methods with SPSS software version 26. The results of the study show that the debt policy variable (DER) has a negative and significant effect on company performance (ROE) and the debt policy variable*economic conditions (DER*KE) has a positive and significant effect on company performance (ROE). This means that when economic conditions are supportive, companies that use debt to finance operational activities or business expansion tend to experience increased performance. Funds obtained from debt can be used for investment, new product development, or market expansion. Proper use of debt can increase a company's return on equity (ROE), as long as the rate of return on the investment financed by debt is higher than the cost of debt. Timing the debt decision is crucial. In improving economic conditions, companies can take advantage of low interest rates and increase production capacity.